PREVALENSI ANEMIA DAN THALASEMIA KARIER PADA KELOMPOK WANITA USIA SUBUR (WUS) - Sukati Saidin; Susi Suwarti Suwardi; Ance Murdiana; Reviana Christiani; Sri Martuti; Joko Pambudi; Muhilal Muhilal (Persagi, 2001)
PREVALENSI ANEMIA DAN THALASEMIA KARIER PADA KELOMPOK WANITA USIA SUBUR (WUS)